Mechanisms for microstructural evolution of FeSiCrNi high silicon steel subjected to thermomechanical processing - Hao Feng; Tao Wang; Jianchao Han; Shuyong Jiang; Bingyao Yan; Dong Sun; Peng Lin; Lifei Wang; Liping Bian; Junbo Yu; Yanqiu Zhang (Materials & Design, 2024)
Fe-6.5 wt% Si high silicon steel alloy presents excellent soft magnetic performances, but a poor plasticity limits its industrial application seriously. In this work, a novel FeSiCrNi alloy with the chemical composition of Fe-6.5Si-2Cr-12Ni (wt%) is designed and subjected to thermomechanical processing including local canning compression at room temperature and annealing at elevated temperatures. It is observed that microstructures of FeSiCrNi specimens with a compression degree of 70 % are dominated by dislocation cells. The microstructural evolution is transformed from static recovery to static recrystallization when FeSiCrNi specimens are annealed from 400 to 700 °C. Grains with high strain energy are successively nucleated via the integration of subgrain boundaries at 600 °C and a pronounced growth of recrystallized grains occurs at 700 °C. In particular, microtextures of the FeSiCrNi alloy essentially consist of γ-fiber ({111}∥ND) and λ-fiber ({100}∥ND) textures during recovery and recrystallization. The intensity of λ-fiber texture is weakened with increasing annealing temperature, while the intensity of γ-fiber which is composed of {111} 〈112〉 and {111} 〈110〉 textures is strengthened. The intensity of {111} 〈112〉 texture within the recrystallized FeSiCrNi grains reaches the maximum value at 700 °C.